Holocord syringomyelia caused by tethered cord syndrome: case report and literature review - Longtao Zheng; Zhangzheng Liao; Hongzhou Duan (BMC Neurology)
Abstract Background Syringomyelia is a rare disease with diverse etiologies, and the syrinx is typically confined to certain segments of the spinal cord. Case of syringomyelia affecting the whole cord due to tethered cord is extremely rare, and the underlying pathophysiological mechanisms remain poorly understood. Case presentation We described an 18-year-old male patient who presented with progressive weakness in both lower extremities and bladder dysfunction over the past four years. Magnetic resonance imaging (MRI) of the entire spine revealed a tethered spinal cord with a large syrinx extending from C1 to L5. Common causes of syrinx such as Chiari malformation, intramedullary tumors and spinal cord injury were systematically ruled out, leading to a strong suspicion that the tethered cord was the primary etiology of the extensive syringomyelia. After undergoing un-tethering surgery, the patient experienced significant symptomatic improvement, and the subsequent follow-up MRI examinations demonstrated a remarkable reduction and eventual resolution of the large syrinx. Conclusions Although rare, tethered cord syndrome can serve as the sole etiology for extensive syringomyelia. For such patients, performing un-tethering surgery can lead to complete resolution of the syrinx and achieve a satisfactory clinical outcome.